2014
DOI: 10.1111/mmi.12736
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of host genes that affect acquisition of an integrative and conjugative element in Bacillus subtilis

Abstract: Summary Conjugation, a major type of horizontal gene transfer in bacteria, involves transfer of DNA from a donor to a recipient using donor-encoded conjugation machinery. Using a high throughput screen (Tn-seq), we identified genes in recipients that contribute to acquisition of the integrative and conjugative element ICEBs1 by Bacillus subtilis. We found that null mutations in some genes caused an increase, and others a decrease in conjugation efficiency. Some mutations affected conjugation only when present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 89 publications
3
68
0
Order By: Relevance
“…Previously, we found that mprF and several other genes involved in the synthesis of phospholipids affect the efficiency of conjugation (20). MprF catalyzes addition of a lysyl group from Lys-tRNA Lys to phosphatidylglycerol to form lysyl-phosphatidylglycerol ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we found that mprF and several other genes involved in the synthesis of phospholipids affect the efficiency of conjugation (20). MprF catalyzes addition of a lysyl group from Lys-tRNA Lys to phosphatidylglycerol to form lysyl-phosphatidylglycerol ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The unmarked ⌬mprF459 allele was constructed by replacing mprF with cat flanked by lox sites to generate strain CMJ459 and then recombining out the lox-cat allele using Cre recombinase expressed from pDR244, as previously described (20,26). The genomic boundaries of this allele are the same as for the ⌬mprF125::mls and ⌬mprF162::spc alleles.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations